Analysis of microbial communities in Binh Chau hot spring through metagenomic DNA sequencing - Thuy, Tran Thanh; Lan, Nguyen Ngoc; Tung, Nguyen Van; Man, Tran Dinh; Hoang, Nguyen Huy; Thoa, Nguyen Kim (Vietnam Journal of Biotechnology, 2022)
Binh Chau hot spring locates in Bung Rieng commune, Xuyen Moc district, Ba Ria - Vung Tau province, and is the second hottest hot spring in Vietnam. Up to date, the microbial diversity of this hot spring has been mainly evaluated using the culture-dependent methods, thus, it could not be able to assess all of microorganisms there. In this report, the microbial community of Binh Chau hot spring was investigated by meta-analysis using Hiseq Illumina for sequencing. The results revealed that only 106,903 genes were annotated and 49,190 genes were unknown among 156,093 potential ORFs. The annotated genes consisted of 29,069 bacterial genes, 1,416 archaeal genes, 4 eukaryotic genes, 3 viral genes, and 76,411 unclassified genes. Among the annotated and classified genes, the microbial community of Binh Chau hot spring was characterized by the predominance of bacteria over archaea. At the phylum level, the most abundant phyla in Binh Chau hot spring were followed as Proteobacteria > Firmicutes > Cyanobacteria > Bacteroidetes > Planctomycetes > Thaumarchaeota > Actinobacteria > Euryarchaeota. These belonged mainly to the thermophilic group. A number of the phyla are reported to grow at high temperature, alkaline pH, and high salt concentrations. In addition to the culturable species, the metagenomic data is also indicated the presence of unculturable groups, for example phylum Acidobacteria and Chloroflexi of bacteria. The order Thermoplasmata, which is classified to class Thermoplasmatales of the phylum Euryarchaeota, as well as ultra-small cell and symbiotic archaea including phyla Parvarchaeota, Nanohaloarchaeota, and Nanoarchaeota were detected. The results in this study indicated an important insight into the microbial communities of Binh Chau hot spring, which revealed a promising thermophilic gene sources for their exploitation and conservation in Vietnam.